Helioseismology, asteroseismology, and MHD connections - Gizon, Laurent (Springer, 2017)
This volume presents a timely snapshot of the state of helio- and asteroseismology in the era when the SOHO/MDI instrument is about to be replaced by SDO/HMI and the CoRoT space mission is yielding its first long-duration light curves of thousands of stars. The articles and topics in this book are inspired by two seminal conferences, HELAS II and SOHO19/GONG 2007, but contributions from other experts have been commissioned as well. For example, three key papers were invited to describe the current status of asteroseismology, global helioseismology, and local helioseismology. These papers provide a framework for the other contributions and together they form a complete description of our understanding of pressure waves in the Sun and other stars.